2010
DOI: 10.1007/s11999-010-1405-6
|View full text |Cite
|
Sign up to set email alerts
|

Site-dependent Replacement or Internal Fixation for Postradiation Femur Fractures After Soft Tissue Sarcoma Resection

Abstract: Background High-dose radiation retards bone healing, compromising the surgical results of radiation-induced fractures. Prosthetic replacement has traditionally been reserved as a salvage option but may best achieve the clinical goals of eliminating pain, restoring function and avoiding complications. Questions/purposes We asked whether patients undergoing prosthetic replacement at index surgery for radiationrelated subtrochanteric or diaphyseal fractures of the femur had fewer complications than those undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
(38 reference statements)
2
16
0
Order By: Relevance
“…e maturation of the mineral in bone is indicated by the changes in the phosphate and carbonate modes. is change of carbonate-to-phosphate ratio is consistent with some studies such as bone tissue maturation [28] and mineralization of developing bone [29]. Meanwhile, this result indicated that an increase in carbonate occurs with increasing mineralization in bone tissue [1].…”
Section: Resultssupporting
confidence: 88%
“…e maturation of the mineral in bone is indicated by the changes in the phosphate and carbonate modes. is change of carbonate-to-phosphate ratio is consistent with some studies such as bone tissue maturation [28] and mineralization of developing bone [29]. Meanwhile, this result indicated that an increase in carbonate occurs with increasing mineralization in bone tissue [1].…”
Section: Resultssupporting
confidence: 88%
“…In the clinical situation, prophylactic intramedullary nailing of the femur is often carried out to prevent fracture in sarcoma patients who are at risk. However, fractures have been reported in patients who have prophylactic intramedullary nails in place, which reflects the significant biological effect of the radiation . Fractures that occur despite prophylactic nailing also indicates the importance of elucidating a biological mechanism and solution to this clinical problem.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 13 reported on 36 fractures of the femur after surgical resection and radiotherapy. The authors compared 30 patients treated by internal fixation to a subgroup of six patients treated with a primary endoprosthesis; 19 of the 30 patients (63%) treated by internal fixation developed a nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…11 When they occur in the femur they represent a major clinical problem as they are painful and debilitating: complications are common despite treatment by internal fixation. 10,13 The purpose of this study was to assess the clinical outcome of patients with a radiationinduced pathological fracture of the femur treated by internal fixation. Our hypothesis was that these fractures have an exceptionally low potential to heal and that many patients would develop a nonunion after internal fixation, requiring further surgery.…”
mentioning
confidence: 99%